Economic feasibility of a photovoltaic energy system for broiler chicken production: a case study - Souza, Vanessa; Gimenes, Régio Marcio Toesca; Sabbag, Omar Jorge [UNESP] (My University, 2023)
The objective is to analyze the economic viability of investing in a photovoltaic energy production system connected to the grid in a poultry farm in the Dark House system, located in the municipality of Dourados, Mato Grosso do Sul, Brazil. The research was developed from a case study. As a criterion for assessing economic viability, the techniques of Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Cost-Benefit Ratio (B/C), Discounted Payback (DP) and Uniform Annual Equivalent Value (AEV), through the determination of a Minimum Rate of Attractiveness adjusted to the risk of emerging countries of 20.11% per year. The initial investment for the implementation of the project was estimated at U$101,939.88 (installation in the aerial part) and U$111,993.91 (installation in the ground). The feasibility analysis showed the following results for the installation of the system in the aerial part of the aviaries: NPV of U$20,105.54, IRR of 24.90%, PI of 1.20, B/C of 3.74, DP of 8.12 years and AEV of U$4,319.77. For ground installation, the results were as follows: NPV of U$9,700.57, IRR of 22.23%, PI of 1.09, B/C of 3.71, DP of 10.62 years and AEV U$2,084.21. In this way, it is concluded that the production of photovoltaic energy in the production of broiler chicken is economic feasible in both evaluated production systems.
Keywords: Aviculture; Costs; Economic viability; Energy sustainability; Investments; Profitability